2008
DOI: 10.1021/ic801376p
|View full text |Cite
|
Sign up to set email alerts
|

Emissive Chromium(III) Complexes with Substituted Arylethynyl Ligands

Abstract: Arylethynylchromium(III) complexes of the form trans-[Cr(cyclam)(CCC(6)H(4)R)(2)]OTf (where cyclam = 1,4,8,11-tetraazacyclotetradecane, R = H, CH(3), or CF(3) in the para position, and OTf = trifluoromethanesulfonate) have been prepared and characterized by IR spectroscopy and X-ray diffraction. The complexes are emissive with excited-state lifetimes in a deoxygenated fluid solution between 200 and 300 micros.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 29 publications
7
35
0
Order By: Relevance
“…Based on these findings and previous studies, the observed emissions are assigned as 2 T 1g → 4 A 2g ( O h ), due to the redshift of the emissions compared to value of the traditional 2 E g → 4 A 2g emission, closer to 700 nm , . Theory suggests that assignment as 2 T 1g emitters implies a difference in π effects of the axial and equatorial ligands, such as a tetraamine complex (σ‐donating) with two π‐donors in the axial positions , . It is well established that the acetylide ligands are π‐donating in metal alkynyl complexes, and this is especially true with an electron deficient Cr III center …”
Section: Resultssupporting
confidence: 57%
“…Based on these findings and previous studies, the observed emissions are assigned as 2 T 1g → 4 A 2g ( O h ), due to the redshift of the emissions compared to value of the traditional 2 E g → 4 A 2g emission, closer to 700 nm , . Theory suggests that assignment as 2 T 1g emitters implies a difference in π effects of the axial and equatorial ligands, such as a tetraamine complex (σ‐donating) with two π‐donors in the axial positions , . It is well established that the acetylide ligands are π‐donating in metal alkynyl complexes, and this is especially true with an electron deficient Cr III center …”
Section: Resultssupporting
confidence: 57%
“…In addition to the aforementioned study of Ru 2 -based acetylides, our laboratory has investigated a number of M III -cyclam (M = Cr, Fe and Co; cyclam = 1,4,8,11tetraazacyclotetradecane) based acetylide complexes, and elucidated their structural and voltammetric properties [34][35][36][37]. It should be noted that other laboratories have also explored the acetylide chemistry of M III -cyclam complexes [38][39][40][41][42][43]. [45].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, complexes trans-[Cr(cyclam)(CC-C 6 H 4 R) 2 ] + appear to be photostable. 46 In CH 2 Cl 2 , some photoreactivity is observed for fac-Cr(ppy) 3 (ESI, Fig. S20).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%